Derechos culturales o de la distribución inequitativa de lo sensible. (2011)
This paper resumes the fundamental motives of an important discussion in the realm of culture: the nature of cultural rights. To think about the phenomenon of cultural rights as a problem of access to the entertainment industries, would be but a poor view of the real issue. Therefore, the author brings the discussion out from the juridical frame into the more comprehensive realm of politics and epistemology, in order to underline a critical posture concerning the issue of accessing to culture as if to a merchandise, and to bolster the alternative of acknowledging culture as an epistemological problem, from the category of representation.